A comprehensive review of oncogenic Notch signaling in multiple myeloma - Justin Roosma (PeerJ)
Multiple myeloma remains an incurable plasma cell cancer with radical case-by-case heterogeneity. Because of this, personalized and disease-specific biology of multiple myeloma must be understood for the discovery of effective molecular targets. The highly evolutionarily conserved Notch signaling pathway has been extensively described as a multifaceted driver of the multiple myeloma disease process—contributing to both intrinsic effects of malignant cells and to widespread remodeling of the tumor microenvironment that further facilitates disease progression. Namely, Notch signaling amongst malignant cells promotes increased proliferation, tumor-initiating capacity, drug resistance, and invasiveness. Moreover, Notch signaling between malignant cells and cells of the tumor microenvironment leads to increased osteodegenerative disease and angiogenesis. This comprehensive review will discuss both the intrinsic implications of pathological Notch signaling in multiple myeloma and the extrinsic implications of Notch signaling in the multiple myeloma tumor microenvironment. Additionally, the genetic origins of Notch signaling dysregulation in multiple myeloma and current attempts at targeting Notch therapeutically will be reviewed. While the subject has been reviewed previously, recent developments in the intervening years demand a revised synthesis of the literature. The aim of this work is to introduce and thoroughly synthesize the current state of knowledge in this vein of research and to highlight future directions for both new and in-the-field scientists.